(untitled) (International journal of artificial intelligence, 2026)
This study is devoted to a comprehensive investigation of the clinical course and diagnostic characteristics of chronic hypertrophic gingivitis in adolescents. The research analyzes etiological factors, pathogenesis, clinical manifestations, and contemporary diagnostic approaches, including clinical indices and instrumental methods. Based on the obtained findings, criteria for early diagnosis have been identified, and evidence-based approaches to effective treatment and prevention have been substantiated.